Case report of a child with combined genetic pathology: cystic fibrosis and facioscapulohumeral progressive muscular dystrophy - O. A. Klochkova; A. L. Kurenkov; A. M. Mamedyarov; H. M. Karimova (Нервно-мышечные болезни, 2015)
The article presents a rare case of a child with a laboratory confirmed combination of several inherited diseases: cystic fibrosis (mutations F508del and E92K) and facioscapulohumeral progressive muscular dystrophy (FSHD). Through the example of the case authors describe the clinical findings of the infantile form of FSHD and the results of prolonged patient’s follow-up. Own clinical data are compared to the literature review. There is also a discussion about genetic heterogeneity of FSHD and complex rehabilitation approaches in case of associated genetic pathology.